Report on Cascading Gender-Responsive and Nutrition-Sensitive Training to Vegetable Business Networks (VBN) Group Members - Ketema, Dessalegn M.; Nchanji, Eileen; Cosmas, Lutomia; Hailu, Shimelis; Asrat, Alemayehu; Jaleta, Gemechis; Zewudie, Yidnekachew (CGIAR Initiative on Gender Equality, 2024)
The Gender Equality Initiative (HER+) is closely working with the Veggies for Planet and People (V4P&P) project implemented by the World Vegetable Centre and the Netherlands Development Organization to improve vegetable production, consumption, and marketing. We are doing this by developing actionable solutions to enhance climate resilience, nutrition, and the empowerment of women in Africa. As one-size-fits-all solutions do not exist, HER+, working with multiple stakeholders, is co-developing diverse scenarios for bundling sociotechnical innovations within Vegetable Business Networks (VBNs) in our two learning labs.